Clinical value of soluble CD40 ligand in coronary heart disease patients - O. P. Shevchenko; O. F. Prirodova; A. O. Shevchenko (Кардиоваскулярная терапия и профилактика, 1970)
Inflammation and thrombosis play an important role in pathogenesis of various cardiovascular diseases (CVD). The studies on atherosclerosis and acute coronary syndrome (ACS) pathogenesis have demonstrated the interaction of these two systems. One of the mechanisms linking inflammation and thrombosis is activation of signal system CD40/CD40L. CD40 and CD40 ligand (CD40L) are transmembrane glycoproteins, related to tumor necrosis factor (TNF) receptor family and TNF family, respectively. CD40 and CD40F are expressed by various cells, including atherosclerotic plaque cells: В-lymphocytes, macrophages/monocytes, endotheliocytes and smooth myocytes. Recently, it has been discovered that platelets can be a source of soluble CD40L form (sCD40FL. In recent clinical trials, diagnostic and prognostic role of sCD40L had been studied in patients with coronary heart disease (CHD). In individuals with myocardial infarction and unstable angina, sCD40L levels are significantly higher than in healthy persons or patients with stable angina. Prognostic sCD40L value was investigated in healthy women and ACS patients; high sCD40L levels independently predicted increased CVD risk. Raised plasma levels of sCD40L are associated with restenosis after balloon coronary angioplasty. Moreover, sCD40L concentrations are increased in Type 1 and 2 diabetes mellitus, hypercholesterolemia, acute cerebral ischemia, smoking, primary and secondary pulmonary hypertension. Therefore, sCD40L could be regarded as inflammation and thrombosis marker. Its increase is a CVD risk factor, associated with poor prognosis in CHD patients.